Crisis y reestructuración financiera: el papel de la banca central - Stiglitz , Joseph (2001)
There vaists a crucial role fu ws Central Bank to play under the dollarization regime in Ecuador. Even though dollarization reduces one source of risk premium, which is the one associated with exchange rate actuations, it doesn't imply economic stability, as the financial crises and economic fuctuations that the world economy experienced under the gold standard in the 19 and carly 20th centuries show. Macroeconomics is about dynamics, unstable processes, rigidities, incomplete information, and imperfect and often irrational markets, and these realities imply the need tor the government to intervene in order to reduce macroeconomic instability and generate stable and desired dynamics in markets. in the specific case of the Central Bank, in order to avoid supply shocks related to the availability of credit, (given that the supply ol credit is an essential ingredient of the supply side of any economy), the Central Bank has a critical role in making credit available and in reasonable terms to the economy in general